Transformational Leadership and Internal Communication Strategies of the staff in the company of engineers and consultants in Callao - Vargas Lasteros, Yesenia Sujey; Pérez Urrutia, Carlos Luis; Flores-Dianderas, Katherine Roxana (LACCEI, 2024)
This study collected data using Google Forms surveys distributed to 65 employees of A&Q Engineers and Consultants. The results were presented sequentially, following an order based on correlations and frequency tables. The analysis indicated that a high percentage of employees consistently perceived a high level of transformational leadership and internal communication strategies. A significant correlation was found between transformational leadership and internal communication strategies, as well as moderate correlations between transformational leadership and the dimensions of interpersonal, intrapersonal, and assertive communication. It is recommended that the company continue to strengthen its internal communication strategies to maintain a strong market performance. Despite the positive results, limitations were identified in background research and data collection, attributable to the geographic dispersion of employees.